Identification of Gastropod from the Air Hitam River Pekanbaru - Wenny Lestari Tarigan; Efawani '; Eddiwan ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The area around Air Hitam river has been used for settlements. Remains of domestic activities may enter and pollute the water. The pollutant may disturb the life of aquatic organism, especially gastropod. This research aims to identify gastropod that lives in the Air Hitam River. This research was conducted at the Air Hitam River Pekanbaru in April-June 2016. There were three sampling stations namely Stasion I (in the up-stream), Stasion II (middle), and Stasions III (downstream). Samplings were conducted 3 times, once/week. Results shown that there are six species of gastropod lived in the Air Hitam River, namely Bellamya sp., Pila globosa., Melanoides prashadi, Gyraulus sp., Thiara riqueti and Lymnaea persica. The water quality parameters are as follows: temperature 290C, turbidity 7.54-15.83 NTU, depth 17-24.5 cm, current speed 12.5-25 cm/s, pH 6, dissolved oxygen 2.02-5.05 mg/L, and free carbon dioxide 9.9-11.9 mg/L.Keywords : Gastropod, Air Hitam River, Melanoides sp., Thiara sp., Lymnaea sp